RISK FACTORS OF PELVIC FLOOR DYSFUNCTION AND THE COMPUTER PROGRAM OF ITS PREDICTION IN WOMEN IN THE PERMANENT PERIOD - Хапачева, Светлана Юрьевна; Артымук, Наталья Владимировна (Medicine in Kuzbass, 2021)
Objective to assess risk factors for pelvic floor dysfunction and develop a computer program for predicting it in women in the postpartum period Materials and methods. Study design: retrospective, case-control. The study was approved by the Ethics Committee of the Kemerovo State Medical University. An anonymous survey was conducted of 80 women with pelvic dysfunction and 80 women without pelvic floor dysfunction at the age from 18 to 45 years (mean age – 31.9 ± 5.9 years, 28.7 ± 5.4 years, p = 0.007). Results. The main risk factors for pelvic floor dysfunction in women of reproductive age, in addition to the generally accepted ones, are the presence of hypodynamia (χ2 = 19.61; p < 0.001) and smoking (χ2 = 14.95; p < 0.001). Application of the computer program «Prediction of Pelvic Floor Dysfunction after Childbirth», developed using binary logistic regression and including 7 factors (the number of births and pregnancies in history, the presence of hypodynamia, obesity, smoking, stigma of connective tissue dysplasia, isthmic-cervical insufficiency) has a sensitivity of 85.0 % and specificity 78.8 % in predicting symptoms of pelvic floor dysfunction in the postpartum period. Conclusion. Thus, as a result of the study, a highly effective approach has been developed to predict and prevent symptoms of pelvic floor dysfunction in women after childbirth.